Symbiotic nitrogen fixation enhancement due to magnetite nanoparticles - Ghalamboran, M. R. (Cranfield University, 2011)
Population pressure on food production motivates the search for new ways to increase the productivity of arable land, especially land rendered marginal by salinity or aridity. The global thesis motivating this work is that nanotechnology can benefit agriculture. My specific thesis is that that part of nanotechnology concerned with nanoparticle production can benefit soybean yield. I have focused on symbiotic nitrogen fixation, and systematically investigated the effects thereon of magnetite nanoparticles introduced into the rhizosphere.My main finding is that the presence of these nanoparticles increases nodulation -- both the number of nodules and the size of individual nodules. Since the experiments were carried out on plants provided with minimal nutrients, there was no corresponding increase in vegetative growth. Some evidence was obtained for the nanoparticles enhancing the "molecular dialogue" between soybean root and the Bradyrhizobia that become incorporated in the nodules. A secondary finding is that the nanoparticles enhance the growth rate of Bradyrhizobia in culture, which is advantageous for the preparation of inocula. Furthermore, coating soybean seeds with nanoparticles and Bradyrhizobia prior to planting enhances survival of the bacteria, and therefore increases the efficiency of subsequent nodulation.